A critical analysis on the application of domestic violence laws in Malaysia with specific reference to domestic violence laws in United Kingdom / Hamizah Hussein …[et al.] - Hussein, Hamizah; Mohd Ghazali, Mohd Akmal; Ghazali, Nur Amalina; Samian, Nur Atiqah; Mohd Ariffin, Rabiatul Adawiyah (2010)
This project attempts to critically analyse the application of domestic violence laws in Malaysia with specific reference to the domestic violence laws in United Kingdom. Besides that, this research also examines the mechanism used to protect domestic violence victims in Malaysia and compare it to the mechanisms provided in United Kingdom. Data were gathered from the semi structured interviews, books, journals, articles, statutes and internet research. The research concluded that the Domestic Violence Act 1994 is insufficient to combat domestic abuse in Malaysia as compared to United Kingdom and therefore these regulations should be reviewed periodically so that the prevention, safety and protection are kept central in keeping with the spirit of the DVA.